The influence of laser shock peening on corrosion-fatigue behaviour of wire arc additively manufactured components - Ermakova, Anna; Braithwaite, Jarryd; Razavi, Javad; Ganguly, Supriyo; Berto, Filippo; Mehmanparast, Ali (Elsevier, 2023)
The need for increased manufacturing efficiency of large engineering structures has led to development of wire arc additive manufacturing (WAAM), which is also known as direct energy deposition (DED) method. One of the main barriers for rapid adoption of the WAAM technology in wider range of industrial applications is the lack of sufficient performance data on the WAAM components for various materials and operational conditions. The present study addresses this essential need by exploring the effects of laser shock peening surface treatment on corrosion-fatigue crack growth (CFCG) life enhancement of WAAM components made of ER70S-6 and ER100S-1 steel wires. The experimental results obtained from this study were compared with the CFCG trends from nominally identical specimens without surface treatment and prove the efficiency of the examined surface treatment method for corrosion-fatigue life enhancement and crack growth retardation of WAAM built steel components, regardless of the material type and specimen orientation. Furthermore, the residual stresses in the WAAM built specimens with and without surface treatment were measured to validate the influence of beneficial residual stresses, arising from surface treatment, on subsequent CFCG behaviour of the material. The residual stress profiles show the beneficial compressive stress fields in the surface treated areas which result in CFCG life enhancement. The results from this study make significant contribution to knowledge by evaluating the suitability of WAAM built steel components for application in offshore environments.
Keywords: Wire arc additive manufacturing; Corrosion-fatigue; Surface treatment; Laser shock peening; Residual stress